A 47‐year‐old man passing putrid semen through saliva and sweat: A case of Dhat syndrome. (5th December 2021) - Arafat, S. M. Yasir; Mondal, Firoj; Ghimire, Sabina
Abstract: Dhat syndrome is a culture‐bound syndrome in which patients believe that they pass Dhat (semen) with their urine, feces, sweat, and saliva that causes lethargy, apathy, dysphoria, and depression. Here, we report a case of a 47‐year‐old man who presented with complaints of burning sensation in the whole body, especially in the pubic region, and insomnia for the last 5 years. This case could be enlightening for clinicians in South Asia in daily clinical practice and family physicians in Western countries where immigrants from Dhat syndrome prevailing countries could present with complex cultural myths and superstitious beliefs. Abstract : Dhat syndrome is a culture‐bound syndrome in which patients believe that they pass Dhat (semen) with their urine, feces, sweat, and saliva that causes lethargy, apathy, dysphoria, and depression. Here, we report a case of a 47‐year‐old man who presented with complaints of burning sensation in the whole body, especially in the pubic region, and insomnia for the last 5 years. We consider Dhat syndrome as the patient has the belief that he has been losing his semen through his saliva, sweat, feces, and urine, which is the reason for his current illness.